2018
DOI: 10.1128/mbio.00470-18
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli ST131- H 22 as a Foodborne Uropathogen

Abstract: E. coli ST131 is an important extraintestinal pathogen that can colonize the gastrointestinal tracts of humans and food animals. Here, we combined detection of accessory traits associated with avian adaptation (ColV plasmids) with high-resolution phylogenetics to quantify the portion of human infections caused by ST131 strains of food animal origin. Our results suggest that one ST131 sublineage—ST131-H22—has become established in poultry populations around the world and that meat may serve as a vehicle for hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
220
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(226 citation statements)
references
References 74 publications
(79 reference statements)
6
220
0
Order By: Relevance
“…The CG SNP-based phylogenetic tree of 84 human and animal ST131 isolates analyzed in this study showed (Figure 1) that they are mostly clustered into three well-defined clades (A, B, and C), and similarly to Petty et al (2014) study, we have observed that clade A is the most divergent from clades B and C. Our results also agree with those published by other authors (Ben Zakour et al, 2016;Matsumura et al, 2017;Liu C. M. et al, 2018;Decano and Downing, 2019) regarding that clade B isolates are displayed into multiple subclades. We identified the six subclades (B0, B1, B2, B3, B4, and B5) described by Ben Zakour et al (2016) and five new ones (B6, B6-like, B7, B8, and B9).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The CG SNP-based phylogenetic tree of 84 human and animal ST131 isolates analyzed in this study showed (Figure 1) that they are mostly clustered into three well-defined clades (A, B, and C), and similarly to Petty et al (2014) study, we have observed that clade A is the most divergent from clades B and C. Our results also agree with those published by other authors (Ben Zakour et al, 2016;Matsumura et al, 2017;Liu C. M. et al, 2018;Decano and Downing, 2019) regarding that clade B isolates are displayed into multiple subclades. We identified the six subclades (B0, B1, B2, B3, B4, and B5) described by Ben Zakour et al (2016) and five new ones (B6, B6-like, B7, B8, and B9).…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with previous studies, plasmids carrying virulence genes belong to the IncF family Nicolas-Chanoine et al, 2017). All the IncF plasmids found in this study conserved the ColV region, frequently detected among avian pathogenic E. coli (APEC) (Liu C. M. et al, 2018). This region comprises the iss (increased serum survival) gene, the iroBCDEN gene cluster (encoding the salmochelin siderophore system present in Salmonella enterica spp.…”
Section: Discussionsupporting
confidence: 88%
“…It is firstly identified in 2008 and now disseminated globally [5]. E. coli ST131 is becoming the predominant extraintestinal pathogenic E. coli lineage and can cause many clinical infections, such as sepsis and urinary tract infections [6]. E. coli ST131 are usually reported to produce extended spectrum β-lactamases and show resistance to fluoroquinones [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Strain designation, sample source, and O serotype are shown. e analysis of the bands generated was performed using the Dice coefficient and unweighted pair group method 6. Canadian Journal of Infectious Diseases and Medical Microbiology…”
mentioning
confidence: 99%
“…Second, the lower virulence may actually confer an additional evolutionary advantage to clade C. According to the trade-off theory (44), host exploitation by a pathogen evolves to an optimal level under a balance between the benefits in terms of transmission and the costs in terms of host mortality (45). Thus, lower virulence could confer improved fitness overall by avoiding symptomatic infections (46, 47), even if it comes at the cost of lower colonisation ability.…”
Section: Discussionmentioning
confidence: 99%